Pilkada Serentak di Masa Pendemi Covid-19: Strategi Marketing Politik Pemenangan Andreas Paru dan Raymundus pada Pilkada Kabupaten Ngada Tahun 2020 - Wateng Due, Apolinaris; Syafruddin, Akhmad (Journal of Politics and Policy, 2023)
This study aims to explain the political marketing strategy used by the candidate pair Andreas Paru and Raymundus Bena or the AP-RB in winning the 2020 simultaneous regional elections in Ngada Regency. This research uses a qualitative approach with a descriptive type that aims to describe the winning strategy obtained during the covid-19 pandemic. The results showed that the political marketing strategy used by the AP-RB was to deliver political products offered directly to prospective voters (Push Political Marketing) by conducting limited socialization of 50 people according to health protocols, the use of social media (facebook) AP-RB group by the success team initiated by the supporting parties PKB and Golkar to deliver political products by printing brochures, pamphlets, and billboards containing the vision-mission and work programs offered. In addition, the success team conducted a segmentation strategy based on geography, psychography, behavior and socio-culture to determine the political map which was then used as the candidate's supporting vote base. Determining targeting and positioning to bring up a certain image to voters both through work programs (policies) about TANTA NELA PARIS, namely Farmers Livestock Fishermen and Tourism, candidate profiles (person). This study also found that the influence of political parties (price) has a very important role in creating a good image among the public.